The Improvement of The Learning in Asking and Giving Opinion through Cooperative Learning Model - Hesti Utari (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2022)
This study aims to improve greetings in English language learning through theCooperative Learning Model. Students are expected to easily absorb the material provided by the teacher during learning. The method used was the Classroom Action Research (CAR) with quantitative descriptive research approach is a way of determining how to obtain data on these variables through cycles In research activities, how to obtain this data is known as the data collection method. The research subjects were eight grade of A which amounted to 32 students at SMPN 4 Sungai Raya, Kubu Raya. Based on the results of the research during the Pre-Cycle, among 32 students, 14 students passed with a percentage of 43%. There were 26 students passed with a percentage of 81% in Cycle I and continuedCycle II with improved planning and implementation of learning, especially improving the lesson plan accurately and on target using Cooperative Learning Model. There were 30 students have passed with a percentage of 93% and 7% or 2 students who have not passed. Through the implementation of Cooperative Learning Model, students can understand the topics well because of smaller groupings. It was effective because if there are difficulties for students during learning, they can provide information to each other through questions and answers with students and with the teacher directly.